The abyss beyond dreams : a novel of the Commonwealth - Hamilton, Peter F. (Commonwealth: chronicle of the Fallers, 2014)
"The wait is over. Bestselling science fiction master Peter F. Hamilton is back with the first of a new two-book saga set in his popular Commonwealth universe. Distinguished by deft plotting, a teeming cast of characters, dazzling scientific speculation, and imagination that brings the truly alien to life, The Abyss Beyond Dreams reveals Hamilton as a storyteller of astonishing ingenuity and power. The year is 3326. Nigel Sheldon, one of the founders of the Commonwealth, receives a visit from the Raiel--self-appointed guardians of the Void, the enigmatic construct at the core of the galaxy that threatens the existence of all that lives. The Raiel convince Nigel to participate in a desperate scheme to infiltrate the Void. Once inside, Nigel discovers that humans are not the only life-forms to have been sucked into the Void, where the laws of physics are subtly different and mental powers indistinguishable from magic are commonplace. The humans trapped there are afflicted by an alien species of biological mimics--the Fallers--that are intelligent but merciless killers. Yet these same aliens may hold the key to destroying the threat of the Void forever--if Nigel can uncover their secrets. As the Fallers' relentless attacks continue, and the fragile human society splinters into civil war, Nigel must uncover the secrets of the Fallers--before he is killed by the very people he has come to save. Praise for Peter F. Hamilton's Great North Road "Gripping. a mammoth tale featuring believable characters and exceptionally skilled storytelling."--Library Journal (starred review) The Evolutionary Void "Satisfying and powerful. Space Opera doesn't get much more epic."--SFFWorld The Temporal Void "Fusing elements of hard SF with adventure fantasy tropes, Hamilton has singlehandedly raised the bar for grand-scale speculative storytelling."--Publishers Weekly The Dreaming Void "A real spellbinder from a master storyteller. dozens of scenarios, a surprisingly well-delineated cast of thousands, plotting enough to delight the most Machiavellian of readers."--Kirkus Reviews (starred review)"--